Ombudsman for Good Governances in Ethiopia: Assessing the Awareness and Perceptions of Civil Servants: Insight from South Wollo Zone Civil Servants (Global Journal of Human-Social Science, 2018)
The existence of Ombudsman promotes good governance around the world by ensuring administrative accountability and transparency. The necessity for the office of Ombudsman has been felt in Ethiopia ever since 1991 and the 1995 FDRE Constitution makers incorporated provision for democratic institutions in Article 55 of the constitution. In 2000, the parliament in Ethiopia passed the Ombudsman Act in pursuance of Article 55 of the FDRE constitution. The objective of this paper is to provide an analytical overview of the awareness and perceptions of civil servants about Ethiopian Ombudsman institution as a mechanism of good governance by focusing on south wollo zone civil servants. To achieve this objective explanatory research approach was used. First quantitative data collected and followed by qualitative data. The quantitative data interpreted using SPSS version 20 and verified against qualitative data and existing literature. Using these researcher reach upon the following finding. Thus, the finding shows that although the importance of ombudsman as mechanism of promoting good governance is accepted as indispensable part of democratization process, the office, however, has not yet been reach grass root level and the provisions of the act have remained as dead letters.
Keywords: ombudsman; good governance; perception of civil servants; awareness of civil servants